KEWAJIBAN YAYASAN ATAS JAMINAN SOSIAL KETENAGAKERJAAN KEPADA TENAGA PENDIDIK DI KABUPATEN SIDOARJO - Hermawan, Luqman Anjas (Universitas Negeri Surabaya, 2020)
Social security organized by the Social Security provider of human resources (BPJS employment) is a government program in seeking protection for the workforce, participants of BPJS employment consist of workers and employers, employers who do not register themselves and workers into BPJS employment has violated the provisions of article 15 paragraph (1) of Law Number 24 of 2011 about BPJS, Registration of BPJS Employment membership can only be done by the employer gradually. This research aims to analyze the implementation of the obligations of the Foundation in the registration of social security rights of employment to its human resources based on the provisions of the law. The research method used is empirically based on data collection for problem solving, is descriptive in the observation of the real symptoms in human life. The results showed that 2 the foundations did not register educators to BPJS employment and replaced them with other benefits, as well as one of the foundations to enter into additional agreements to agree on this subject, this additional agreement was carried out by the foundation with its educative power after the main agreement of acceptance of workers. The foundation's decision-making does not register educators with the financial basis of an unstable foundation in every development, this makes one of the educator's rights unfulfilled. Employment Social security rights in relation to educators welfare.